Pengaruh Current Ratio, Return on Asset, Debt to Equity, dan Kepemilikan Institusional Terhadap Nilai Perusahaan - Apriliana, Apriliana; Martini, Martini (CNPLUS Publisher, 2024)
This study aims to determine the effect of current ratio, return on asset, debt to equity ratio, and institutional ownership on firm value. The population in this study are processed property and real estate companies listed on the Indonesia Stock Exchange in 2018 – 2022 of 85 companies. The sampling technique used was purposive sampling and obtained 38 companies that met the criteria as samples. The data used in this study were obtained from financial report and annual report. The analysis technique used in this study is multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS) version 22. The results of this study indicate that return on asset have a positive and significant effect on firm value, while current ratio, debt to equity ratio, and institutional ownership has no effect on firm value.